Possible neuropsychiatric reaction to high-dose oseltamivir during acute 2009 H1N1 influenza A infection. - Nakamura, K; Schwartz, B; Lindegårdh, N; Keh, C; Guglielmo, B (2010)
The safety of high-dose oseltamivir during treatment of 2009 H1N1 influenza A infection for critically ill patients is unknown. Here we report on a case patient with severe, delayed-onset neuropsychiatric symptoms after administration of high-dose oseltamivir. Clinicians should be vigilant to the possible increased risk of complications associated with high-dose oseltamivir therapy for 2009 H1N1 influenza A infection.